2015
DOI: 10.1117/1.jbo.20.5.056008
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography system requirements for clinical diagnostic middle ear imaging

Abstract: Noninvasive middle ear imaging using optical coherence tomography (OCT) presents some unique challenges for real-time, clinical use in humans. We present results from a two-dimensional/three-dimensional OCT system built to assess the imaging requirements of clinical middle ear imaging, and the technical challenges associated with them. These include the need to work at a low numerical aperture, the deleterious effects of transtympanic imaging on image quality at the ossicles, sensitivity requirements for clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Translating OCT middle ear imaging to the clinic involves a number of challenges [17]. Given the natural curvature and oblique orientation of the human TM relative to the ear canal, and allowing for normal anatomical variability between patients, a practical system must be capable of imaging over a depth range exceeding 10 mm in order to capture the entire middle ear; a range that has not been achievable with spectral-domain systems used in earlier studies [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Translating OCT middle ear imaging to the clinic involves a number of challenges [17]. Given the natural curvature and oblique orientation of the human TM relative to the ear canal, and allowing for normal anatomical variability between patients, a practical system must be capable of imaging over a depth range exceeding 10 mm in order to capture the entire middle ear; a range that has not been achievable with spectral-domain systems used in earlier studies [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these results showed the accuracy of OCT images and the possibility of utilizing the OCT as measuring the middle and inner ear structures. Utility of OCT have been reported to have the ability to show the structures of the inner ear in the mice [15]. Tona et al [16] reported that OCT could evaluate the gross anatomy of mouse cochlea, including the Reissner's membrane and basilar membrane, with results demonstrating endolymphatic hydrops.…”
Section: Discussionmentioning
confidence: 99%
“…Because the light used in OCT should pass through the curvature of the external canal, the OCT system combined with a surgical microscope or endoscope was developed for this purpose [5,[16][17][18][19]. Microscope-integrated intraoperative OCT is already commercially available for imaging of ophthalmic surgical maneuvers [15,16,20]. Garcia et al [21] introduced an intraoperative OCT probe used for vocal fold imaging, which could also be applied to ear imaging if modified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of the eardrum change from person to person, especially during OME since it can become thicker and a biofilm may become attached to it. A wide range of scattering parameters is simulated in order to cover the whole possible range including values estimated in literature of µ s < 22 mm −1 at 1310 nm [9]. Figure 4 shows the signal and SBR for increased scattering coefficient and changed scattering anisotropy of the eardrum.…”
Section: Scattering Of the Eardrummentioning
confidence: 99%